Comparative analysis of acute toxicities and patient reported outcomes between intensity-modulated proton therapy (IMPT) and volumetric modulated arc therapy (VMAT) for the treatment of oropharyngeal cancer. (June 2020) - Manzar, Gohar S.; Lester, Scott C.; Routman, David M.; Harmsen, William S.; Petersen, Molly M.; Sloan, Jeff A.; Mundy, Daniel W.; Hunzeker, Ashley E.; Amundson, Adam C.; Anderson, Jeffrey L.; Patel, Samir H.; Garces, Yolanda I.; et al.
Highlights: Compared to VMAT, IMPT is associated with less PEG placement for the treatment of OPC. IMPT is associated with decreased acute hospitalizations compared to VMAT. Provider-reported acute toxicities show less mucositis, dysphagia, and pain with IMPT. Patient-reported outcomes improved with IMPT included cough and dysgeusia. Benefits were predominantly seen in those treated definitively or with adjuvant CRT. Abstract: Background and purpose: IMPT improves normal tissue sparing compared to VMAT in treating oropharyngeal cancer (OPC). Our aim was to assess if this translates into clinical benefits. Materials and methods: OPC patients treated with definitive or adjuvant IMPT or VMAT from 2013 to 2018 were included. All underwent prospective assessment using patient-reported-outcomes (PROs) (EORTC-QLQ-H&N35) and provider-assessed toxicities (CTCAEv4.03). End-of-treatment and pretreatment scores were compared. PEG-tube use, hospitalization, and narcotic use were retrospectively collected. Statistical analysis used the Wilcoxon Rank-Sum Test with propensity matching for PROs/provider-assessed toxicities, and t -tests for other clinical outcomes. Results: 46 IMPT and 259 VMAT patients were included; median follow-up was 12 months (IMPT) and 30 months (VMAT). Baseline characteristics were balanced except for age ( p = 0.04, IMPT were older) and smoking ( p < 0.01, 10.9% IMPT >20PYs, 29.3% VMAT). IMPT was associated with lower PEG placement (OR = 0.27; 95% CI: 0.12–0.59; p = 0.001) and less hospitalization ≤60 days post-RT (OR = 0.21; 95% CI:0.07–0.6, p < 0.001), with subgroup analysis revealing strongest benefits in patients treated definitively or with concomitant chemoradiotherapy (CRT). IMPT was associated with a relative risk reduction of 22.3% for end-of-treatment narcotic use. Patients reported reduced cough and dysgeusia with IMPT ( p < 0.05); patients treated definitively or with CRT also reported feeling less ill, reduced feeding tube use, and better swallow. Provider-assessed toxicities demonstrated less pain and mucositis with IMPT, but more mucosal infection. Conclusion: IMPT is associated with improved PROs, reduced PEG-tube placement, hospitalization, and narcotic requirements. Mucositis, dysphagia, and pain were decreased with IMPT. Benefits were predominantly seen in patients treated definitively or with CRT.